Description of Consumption Level of Energy, Protein, and Nutritional Status of Children Under Five at the Orphanage Monitored by Kupang City Social Office - Patricio Lourenco Andre Mendonca; Lewi Jutomo; Rut Rosina Riwu (Lontar : Journal of Community Health, 2022)
The low level of public nutrition knowledge related to a balanced diet, a good diet, the presence of poor nutrition areas, and the low level of energy and protein adequacy are the causes of nutritional problems in Indonesia. Children under five years old (toddlers) are included in the vulnerable age group, so they need serious attention in efforts to fulfill their nutritional intake. This study described the energy consumption, protein, and nutritional status of toddlers in the orphanage assisted by the Social Service of Kupang City. This type of research was descriptive quantitative with a cross-sectional study approach. The sampling technique in this study used total sampling so that the total population was the same as the number of samples, namely 34 toddlers. The results showed that the highest energy and protein consumption level was in the deficit and normal category, respectively (59%&41%). Nutritional status based on weight/age and height/age index was in the normal category (94% dan 74%). The weight/height index was in a suitable category (88%). Paying more attention to the nutrition of children under five in orphanages is necessary. The orphanage is expected to play an active role in increasing their attention to the level of energy consumption of toddlers by arranging a balanced nutritional menu so that the energy needs of the toddlers can be fulfilled. In addition, the aid provider, either permanent or non-permanent donors or the community, is expected not to assist the orphanage only during the COVID-19 pandemic.